Chemical Characterization, Antimicrobial, Antioxidant and Cytotoxic Potential of Essential Oils from Perilla frutescens L. found in Nepal - Paudel, Prem Narayan; Shrestha, Anjila; Satyal, Prabodh; Setzer, William N.; Awale, Suresh; Watanabe, Shiro; Maneenet, Juthamart; Satyal, Rakesh; Gyawali, Rajendra (Journal of Nepal Chemical Society, 2025)
Perilla is widely valued for its culinary, aromatic, and medicinal uses. This study was conducted to characterize the chemical components, enantiomeric distribution, and to explore the antimicrobial, antioxidant, and cytotoxic potential of essential oils from Perilla frutescens L. found in Nepal. Essential oils (EOs) obtained through hydrodistillation were analyzed for their chemical constituents using gas chromatography-mass spectrometry (GC-MS), while chiral GC-MS was employed to determine the enantiomeric distribution of chiral terpenoids. The DPPH and ABTS radical-scavenging assays were used to evaluate the antioxidant activities. In vitro antimicrobial activity was performed by microbroth dilution. Cytotoxic activities were determined by cell viability using a Cell Counting Kit assay. GC-MS analyses of three P. frutescens (PEO) samples had 50 to 54 chemical components, consisting of 91.98 to 99.67 %. PEO was characterized as PK type by the most dominant components, perilla ketone (42.26 to 56.26 %), isoegomaketone (23.68-23.85 %), β-caryophyllene (1.33-7.33 %), and isobicyclogermacrene (3.29-5.27 %), respectively. Twelve chiral terpenoids were identified as enantiomeric distribution with 1-octen-3-ol (100 % as dextrorotatory) in all three PEO samples. PEO collected from Bardiya in summer gave the best antioxidant activity against DPPH with an IC50 value of 334.26±0.20 µg/mL and against ABTS with an IC50 value of 93.15±1.04 µg/mL. The antimicrobial inhibition against E. coli, C. albicans, and A. niger was observed, with MICs varying from 156.3 to 625 µg/mL. PEO taken from Kavre in summer showed good cytotoxicity with an IC50 value of 7.41 µg/mL against the NIH-3T3 cell line and an IC50 value of 8.14 µg/mL against the MCF-7 cell line. All three PEOs showed notable chemical complexity and promising biological activities, emphasizing their importance as natural ingredients.